Especie nueva de sanguijuela del género helobdella (rhynchobdellida: glossiphoniidae) del lado de Catemaco, Veracruz, México - Oceguera-Figueroa, Alejandro (Instituto de Ecología, A.C., 2007)
A new leech species of the genus Helobdella from Catemaco Lake, Veracruz, Mexico is described based on the examination of 23 specimens. Leeches were found attached to submerged rocks and plants. The new species lacks a nuchal scute and is distinguishable from other species of the genus by the presence of a obscure dorsal surface with white spots of different size and irregularly arranged; three or five longitudinal rows of dorsal papillae; salivary glands diffused in the parenchyma; six pairs of crop caeca, the posterior pair forming post-caeca or diverticula.